Palestin Dalam Gagasan Pemikiran ‘Abd Al-Salām Yāsīn - Helimy Aris; Adnan Mohd Abdullah Shalash; Syed Najihuddin Syed Hassan; Muhammad Akmaluddin Mohd Hamdan; Norhasnira Ibrahim; Siti Mardhiyah Kamal Azhar (Universiti Sains Islam Malaysia, 2026)
Indexed by MyCite